Inhibition of proliferation and induction of G1-phase cell-cycle arrest by dFMGEN, a novel genistein derivative, in lung carcinoma A549 cells. (April 2013) - Peng, Bo; Cao, Jianguo; Yi, Sisi; Wang, Chengkun; Zheng, Guopei; He, Zhimin
<x xml:space="preserve">Abstract</x> Genistein (GEN) is a molecule of great interest as a potent chemopreventive agent against atherosclerosis and cancer. However, the bioavailability of GEN is very low in vivo. Our previous study showed that a GEN derivative, 7-difluoromethyl-5, 4′-dimethoxygenistein (dFMGEN) has a better bioavailability than GEN in vivo. In this study, we further evaluated the efficacy of dFMGEN as a candidate for cancer therapy. We demonstrated that dFMGEN treatment decreased the viability of A549 cells in a concentration- and time-dependent manner and induced cell-cycle arrest at the G1 phase. G1 phase arrest was correlated with a significant reduction of Cdk4 and cyclin D1 protein level. Further studies showed that cyclin-dependent kinase (Cdk)4 and cyclin D1 protein-level decrease was caused by Cdk inhibitors p15, p21, and p27 level increase, and decreased protein level directly suppressed Rb protein phosphorylation and E2F-1 expression, then cell-cycle progression was arrested. Finally, we also found that dFMGEN has a dosage effect in suppressing tumor growth in vivo, and that dFMGEN was well tolerated by animals. In summary, our results suggest that dFMGEN has therapeutic potential for the treatment of human lung cancer.